The tourist within - Tshering Denkar (Thimphu : Tshering Denkar, 2022)
The tourist within tells myriad stories born of a young woman's lust for travel. From lofty unclimbed mountains to sweltering foothills to the last surviving nomads, the colorful stories capture the diverse physical and cultural landscape of Bhutan. The stories are beautifully strung together by a common narrative thread anchored in the author's keen socio-cultural sensibilities. As diverse as the subjects are what shines through faithfully is the candid tone and unassuming style of writing. This anthology is a tribute to a young woman's passion and fortitude, a small country's beauty and diversity and, above all, the people who populate the stories in this book who made all the travels possible. The reader will be amazed by the variety of stories a small country can contain and the number of stories a single person often travelling solo or hitch-hiking can tell. If you can picture and feel someone being charged at by a raging yak, dismayed by a shrinking river source, exhilarated by her first visit to a palace, you will enjoy this book.